Science experiences for the early childhood years - Harlan, Jean Durgin (New York : Merrill, 1992)
Reflecting the National Science Education Standards, this text takes a hands-on approach to science learning by providing a theoretical foundation and many practical activities. It presents science-concept-based units that offer teachers a way to integrate science knowledge and processes into the whole curriculum.
includes refereance
Keywords: Science -- Study and teaching (Elementary)